Elementary 3D organization of active and silenced E. coli genome - Alexey A. Gavrilov; Ilya Shamovsky; Irina Zhegalova; Sergey Proshkin; Yosef Shamovsky; Grigory Evko; Vitaly Epshtein; Aviram Rasouly; Anna Blavatnik; Sudipta Lahiri; Eli Rothenberg; Sergey V. Razin; et al. (Nature, 2025)
Abstract Unravelling how genomes are spatially organized and how their three-dimensional (3D) architecture drives cellular functions remains a major challenge in biology1,2. In bacteria, genomic DNA is compacted into a highly ordered, condensed state called nucleoid3–5. Despite progress in characterizing bacterial 3D genome architecture over recent decades6–8, the fine structure and functional organization of the nucleoid remain elusive due to low-resolution contact maps from methods such as Hi-C9–11. Here we developed an enhanced Micro-C chromosome conformation capture, achieving 10-base pair (bp) resolution. This ultra-high-resolution analysis reveals elemental spatial structures in the Escherichia coli nucleoid, including chromosomal hairpins (CHINs) and chromosomal hairpin domains (CHIDs). These structures, organized by histone-like proteins H-NS and StpA, have key roles in repressing horizontally transferred genes. Disruption of H-NS causes drastic reorganization of the 3D genome, decreasing CHINs and CHIDs, whereas removing both H-NS and StpA results in their complete disassembly, increased transcription of horizontally transferred genes and delayed growth. Similar effects are observed with netropsin, which competes with H-NS and StpA for AT-rich DNA binding. Interactions between CHINs further organize the genome into isolated loops, potentially insulating active operons. Our Micro-C analysis reveals that all actively transcribed genes form distinct operon-sized chromosomal interaction domains (OPCIDs) in a transcription-dependent manner. These structures appear as square patterns on Micro-C maps, reflecting continuous contacts throughout transcribed regions. This work unveils the fundamental structural elements of the E. coli nucleoid, highlighting their connection to nucleoid-associated proteins and transcription machinery.